ANALISIS EFEKTIVITAS & EFISIENSI PENERIMAAN PAJAK BUMI DAN BANGUNAN SEBAGAI POTENSI PENDAPATAN ASLI DAERAH KABUPATEN NGAWI TAHUN 2018-2020 - Esa Aldila; Suyatmin Waskito Adi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
One of Indonesia's state revenues that is currently being intensively promoted is taxes. Indonesia makes tax as one of the largest sources of income, one of which is local taxes using secondary and premier data. The object of this research is the Ngawi Regency Finance Agency. Meanwhile, the research subjects were employees of the Ngawi Regency Finance Agency who were taken using a sampling technique. The results in this study are the level of effectiveness of Ngawi Regency's PBB revenue for the 2018-2020 period is classified as effective. This is indicated by the percentage of effectiveness with an average of 98.23%, the efficiency level of Tax revenue in Ngawi Regency for the period 2018 to 2020 is classified as efficient, which is indicated by an average efficiency of 5.53%, and Land and Building Taxes are one of the mainstay items of income. region because PBB contributes the largest PAD in the tax sector. This means that the level of efficiency and effectiveness of Land and Building Tax receipts as reviewed in the previous chapter has a positive effect on the potential for Regional Original Income in Ngawi Regency.